2023
DOI: 10.3389/fimmu.2023.1062679
|View full text |Cite
|
Sign up to set email alerts
|

The safety of combining immune checkpoint inhibitors and platinum-based chemotherapy for the treatment of solid tumors: A systematic review and network meta-analysis

Abstract: ObjectiveCombination treatment regimens consisting of both immune checkpoint inhibitors (ICI) and chemotherapeutic agents have emerged as the standard of care for a range of cancers. This network meta-analysis (NMA) examined the toxicity profiles and safety rankings of these different ICI-based combination regimens.MethodsThe PubMed, EMBASE, Web of Science, and Cochrane Library databases were searched for all randomized controlled trials (RCTs) published as of March 1, 2022 comparing two or more treatment regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Several systematic reviews have illustrated the safety profiles of ICIs for cancer treatment at various sites (17,22,(28)(29)(30)(31)(32). Zhou et al (22) comprehensively assessed the incidences and safety profiles of trAEs among various combination therapies based on 161 RCTs and found that all-grade and grade ≥ 3 trAEs were higher for patients receiving PD-1 or PD-L1 inhibitors combined with chemotherapy or targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews have illustrated the safety profiles of ICIs for cancer treatment at various sites (17,22,(28)(29)(30)(31)(32). Zhou et al (22) comprehensively assessed the incidences and safety profiles of trAEs among various combination therapies based on 161 RCTs and found that all-grade and grade ≥ 3 trAEs were higher for patients receiving PD-1 or PD-L1 inhibitors combined with chemotherapy or targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (17) investigated the safety profiles of ICIs for esophageal cancer and found that most AEs of combined therapies were tolerable, and all-grade pneumonitis differed between the PD-1 and PD-L1 inhibitor groups. Mei et al (31) identified 33 RCTs and found that camrelizumab or avelumab combined with chemotherapy showed higher incidences of all-grade AEs, whereas durvalumab and sintilimab could be considered relatively safe PD-L1 and PD-1 inhibitors. Longo et al (16) identified seven RCTs and found that ICI-based combined treatment was associated with a high risk of grade 3-5 trAEs in patients with small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, sintilimab, an anti-PD1 approved in China, was applied in most patients. Although thyroid dysfunction is the most commonly reported irAE of sintilimab [ 29 ], there is limited information available on the effect of thyroid antibodies by sintilimab. Therefore, it is reasonable to speculate that the low positive rate of thyroid antibodies in this study may be related to the use of different ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Fever, caused by a wide variety of reasons, is frequently reported in cancer patients ( 37 ), and fever is one of the most prevalent adverse events after ICIs remedy ( 7 , 8 ). When immunotherapy is combined with other therapy patterns, the incidence of fever increases remarkably.…”
Section: Etiology Of Fever Of Unknown Origin Induced By Icismentioning
confidence: 99%
“…In general, FUO are classified as classic FUO, nosocomial FUO, immunodeficiency-associated FUO, and travel-associated FUO. Given that 1) ICIs are administered more frequently in cancer therapy; 2) pyrexia stands as one of the most common adverse events of ICIs ( 7 , 8 ); 3) patients treated with ICIs face challenges in identifying and discriminating the etiology of FUO, we believe that it is of crucial clinical significance to list ICIs-associated FUO as a separate category of FUO, which is defined as fever during ICIs administration in cancer patients with immune activation, cytokines secretion or pathogen reactivation.…”
Section: Introductionmentioning
confidence: 99%